Recloser-fuse coordination improvement for distributed generation installed capacity enhancement in electrical distribution systems - Autthaporn Supannon (2018)
© 2015 IEEE. This paper presents a new strategy for improving recloser-fuse coordination to enhance distributed generation (DG) installed capacity in medium voltage distribution systems. The proposed algorithm could be used to solve recloser-fuse miscoordination problems based on fuse-saving principles. Moreover, it can increase power transfer capability from DG to load by changing the time dial of the recloser and fuse size simultaneously. This algorithm considers many conditions such as fault locations, DG types, DG locations and DG sizes. The proposed algorithm has been implemented in the practical 22 kV Mae Sariang distribution system of the Provincial Electricity Authority of Thailand (PEA)using DIgSILENT Power Factory software. The test results showed that the proposed method could be used to improve recloser-fuse coordination with a suitable time dial of the recloser and fuse size, resulting in the maximum capacity of DG connected at any location in the distribution system.